Analisis Strategi Pemberdayaan Petani Kopi dalam Meningkatkan Kesejahteraan Melalui Pertanian Berkelanjutan di Tanggamus Provinsi Lampung - M Faiz Nurfatoni; Erlin Kurniati (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
This study aims to analyze the empowerment strategies of coffee farmers in improving welfare through the implementation of sustainable agriculture in Tanggamus Regency, Lampung Province. As one of Indonesia’s key robusta coffee production centers, the region holds significant potential for further development. The research employs a descriptive qualitative approach, utilizing in-depth interviews, direct observation, and documentation involving farmers, farmer group leaders, agricultural extension officers, and other relevant stakeholders. The findings reveal that empowerment strategies have been implemented through training and extension programs, strengthening farmer organizations, enhancing access to financial capital and marketing channels, and adopting environmentally friendly farming practices. These strategies have had a positive impact on farmers, particularly in increasing their knowledge of sustainable agriculture, raising household incomes, and improving overall quality of life. However, several challenges remain, such as low literacy levels among farmers, reliance on middlemen for product distribution, and uneven implementation of support programs across communities. To ensure long-term success, collaboration among local government agencies, farmer groups, and private sector entities is essential. Building strong, integrated support systems will help address existing barriers and encourage broader participation in sustainable coffee farming initiatives ultimately empowering farmers and promoting inclusive agricultural growth in the region.